A New Jersey anthology - Lurie, Maxine N., 1940- (Rivergate Books/Rutgers University Press, 2010)
This anthology contains seventeen essays covering eighteenth-century agrarian unrest, the Revolutionary War, politics in the Jackson era, feminism and the women's movements, slavery from the seventeenth to the nineteenth centuries, strikes and labor struggles, land use and regional planning issues, Blacks in Newark, the current political state of New Jersey, and more.